Towards Sustainable Social Urban Growth: The Effectiveness of Population Management Program – Family Planning Services of Valenzuela City - Dili, Ramces M.; Almazan, Francez Justine A.; Fabroa, Anne Laura D.T.; Torrejos, Jamaica T. (Journal of Multidisciplinary Research Advancements, 2025)
The rapid population growth rate is one of the significant challenges to sustainable development, particularly in an urbanized area of Valenzuela City. Hence, this study aims to evaluate the family planning services of the Population Management Program towards sustainable social urban growth. A mixed-method approach entailed incorporating both qualitative and quantitative analyses. The challenges identified are limited funding, cultural and religious resistance, service accessibility, and inadequate information on family planning services. The study highlighted the significance of PMP Collaborative Governance Framework in interlinkages between institutions of governments, local communities, and academia in building leadership and operational efficiency in population management that can improve delivery of family planning services as well as greater socio-economic benefits of urbanization. The findings of this study showed that services rendered by the family planning program have actually led to increased knowledge in reproductive health, smaller size of households, and socioeconomic conditions of the clients of the three highly dense barangays of Valenzuela City. Collaborative governance is thus deemed an enabling tool that multi-sectoral partnership and community development activities towards sustainable social urban growth. This study provided program action plans for strengthening family planning services under the PMP, emphasizing collaborative practices and community sustainable development through framework. By filling gaps among stakeholders, the PMP can be a model for other fast-growing cities in the Philippines. These findings are essential for policymakers, practitioners, and researchers seeking to reduce the negative impacts of rapid urbanization while promoting socio-economic equity and sustainable development.